Factors associated with the sleep disturbances of people with breast cancer during chemotherapy in China: A cross‐sectional study - Wenjuan Zhu; Wanling Li; Jinnan Gao; Linying Wang; Jun Guo; Hui Yang (Wiley, 2023)
Abstract Aim The aim of the study was to investigate the incidence of sleep disturbance and its relationship with anxiety and depression symptoms, social support and hope in breast cancer patients in China during chemotherapy. Design A single‐centre cross‐sectional study. Methods A total of 329 breast cancer patients were selected via convenience sampling method before they began chemotherapy (n = 115), before the 5th week of chemotherapy (n = 117) or 1 month after chemotherapy ended (n = 97) and administered paper‐and‐pencil questionnaires to evaluate sleep quality, depression and anxiety symptoms, social support and hope. Risk factors significantly associated with sleep disturbance during bivariate were incorporated in the multivariate analysis. Bivariate analyses showed that age, menopausal status, depression and anxiety symptoms, emotional/informational support, tangible support, affectionate support, positive social interaction and total support were predictors of sleep disturbance. Results Sleep disturbance was prevalent in breast cancer patients before (27.0%), during (32.5%) and after (39.2%) chemotherapy, with 37.4%, 41.9% and 52.6% of participants, respectively, reporting sleeping below the recommended 7 h. Only 8.6%-15.5% of patients reported taking sedative‐hypnotic drugs during the chemotherapy. Multivariate analyses found that participants reporting clinically significant anxiety (HADS > 8) were 3.5 times more likely to report sleep disturbance (PSQI > 8) than participants without clinically significant anxiety, and each increment in emotional/informational support was associated with a 9.04% reduced risk of sleep disturbance. Moreover, age was an independent predictor of sleep disturbance during multivariate modelling.